Dental anomalies in a patient with Tyrosinemia type I: first case report in the literature - Martelli-Júnior, Hercílio; Bezerra, Hélen Kaline Farias; Albuquerque, Anna Luiza Braga; Arantes, Rodrigo Rezende; Sales, Marcelo Augusto de Oliveira; Fonseca, Felipe Paiva; Machado, Renato Assis; Simões e Silva, Ana Cristina (Journal of Oral Diagnosis, 2025)
Objective: This clinical report describes a 13-year-old female with a complex medical history and multisystemic symptoms, including lower-extremity deformities, hypercalciuria, low body mass, short stature, abdominal pain, seizures, and hypertension. Case report: Despite an initial clinical diagnosis of nonspecific renal tubular acidosis, further investigation revealed a likely pathogenic homozygous variant in the FAH gene, indicating the diagnosis of tyrosinemia type I (HT1). During the investigation, several dental anomalies were detected in this patient (tooth decay, delayed eruption, hypoplastic enamel, and changes in tooth shape). The patient has been receiving dietary adaptations and electrolyte and alkaline solutions supplementation and is under close medical and dental follow-up care. Practical implications: The aim of this report is to highlight the importance of a thorough investigation and genetic testing in patients with multisystemic symptoms and the possibility of oral manifestations and dental anomalies in association with renal tubular disorders, including Tyrosinemia type I.